Photocatalytic Template Synthesis of Pt Nanocages with Enhanced Electrocatalytic Performance. (1st January 2015) - Shi, Haibo; Ouyang, Shenshen; Peng, Meiling; Wang, Tao; Wang, Sheng
Abstract : In this paper, a simple and efficient photocatalytic template synthesis of well-dispersed 3D platinum nanocages (Pt NCs) was proposed. The synthesis was carried out by using TiO2 nanoparticles not only as photocatalysts but also as template materials. Under UV illumination, Pt nanobranches were first photodeposited on the edge of the TiO2, which formed cage structures with increasing illumination time. As-prepared 3D Pt NCs were self-supporting nanostructures that possessed high surface areas and enough absorption sites for reactant molecules and were shown to be excellent nanoelectrocatalyst for the methanol oxidation reaction (MOR) in comparison with commercial Pt electrocatalysts.